2021
DOI: 10.3389/fpsyg.2021.645032
|View full text |Cite
|
Sign up to set email alerts
|

Learning in Virtual Reality: Bridging the Motivation Gap by Adding Annotations

Abstract: One challenge while learning scientific concepts is to select relevant information and to integrate different representations of the learning content into one coherent mental model. Virtual reality learning environments (VRLEs) offer new possibilities to support learners and foster learning processes. Whether learning in VR is successful, however, depends to a large extent on the design of the VRLE and the learners themselves. Hence, adding supportive elements in VRLEs, such as annotations, might facilitate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 61 publications
(123 reference statements)
0
11
0
3
Order By: Relevance
“…Another study that looked at signals in a VRLE showed an interaction effect on learning outcome with motivation as a moderator. They found that less motivated learners supported by signals achieved a similar learning outcome as intrinsically motivated learners (Vogt et al, 2021a). Chin et al (2015) found similar results in VR lab safety training.…”
Section: Recent Studiesmentioning
confidence: 67%
“…Another study that looked at signals in a VRLE showed an interaction effect on learning outcome with motivation as a moderator. They found that less motivated learners supported by signals achieved a similar learning outcome as intrinsically motivated learners (Vogt et al, 2021a). Chin et al (2015) found similar results in VR lab safety training.…”
Section: Recent Studiesmentioning
confidence: 67%
“…In this study, we explored the effects of cues on learning outcomes and attention allocation in an immersive 360-degree video learning environment. In comparison to previous studies, we focused on finding patterns of attention distribution by using eye-tracking studies (Rupp et al, 2016;Albus et al, 2021;Vogt et al, 2021). The results showed that textual and visual cues positively affected cognition, thereby proving that the signal principle of CTML is also applicable in the immersive 360-degree video learning environment.…”
Section: Discussionmentioning
confidence: 97%
“…Textual cues include headings, annotations, summaries, font colors, text picture references, and intonation (Schneider et al, 2018). Annotations are common textual cues that can highlight the internal relationships between information, support mapping and integration processes, and repeat the crucial terms of the auditory text as needed to help deepen learners' understanding of information (Vogt et al, 2021). A study found that in VR, annotations could improve learners' recall performance and germane cognitive load (Albus et al, 2021).…”
Section: Signal Principle In Multimedia Learningmentioning
confidence: 99%
“…More recent VR studies also used rather short learning units of 7 to 12 min (e.g. Albus et al., 2021; Parong & Mayer, 2018; Vogt et al., 2021). We nevertheless would recommend that future studies might consider investigating longer learning units to investigate even more complex learning processes.…”
Section: Discussionmentioning
confidence: 99%
“…Verbal information might include short narratives, simple labels, or annotations (e.g. Vogt et al., 2021). VRLE might have a high visual load; hence further textual details could be presented as auditory text (e.g.…”
Section: Introductionmentioning
confidence: 99%